Why the rich are getting richer what is financial education...really? - Kiyosaki, Robert T.; Wheelwright, Tom (Plata Publishing, 2018)
In this book, the reader will learn why the gap between the rich and everyone else grows wider; why savers are losers; why debt and taxes make the rich richer; why traditional education actually causes many highly educated people - such as Robert's poor dad - to live poorly. In this book, the reader will find out why going to school, working hard, saving money, buying a house, getting out of debt, and investing for the long term in the stock market is the worst financial advice for most people. In this book, the reader will find out why real financial education may never be taught in schools. In this book, Robert shares the answers found on his life-long search, after repeatedly asking the question, 'When will we learn about money?' In this book, the reader will find out 'What is financial education - really'.